Cybergogy Trends in Cognitive Psychology of Physics Learning: A Systematic Literature Review from 2019-2023 with NVivo - Achmad Samsudin; Hera Novia; Andi Suhandi; Adam Hadiana Aminudin; Muhamad Yusup; Supriyatman Supriyatman; Masrifah Masrifah; Niki Dian Permana; Bayram Costu (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2023)
The purpose of this Systematic Literature Review (SLR) is to identify the cybergogy trends in cognitive psychology in physics learning from 2019-2023. The focus of this review includes research methods, technology used, links to cognitive psychology, and physics concepts. A total of 60 articles (60 articles indexed Scopus and 29 of them indexed Scopus and WoS) were used in this review using the Prisma guide. The analysis was carried out with the help of NVivo12 as well as percentage calculations. The results show that: 1) The research method used is dominated by quasi-experiments (22%); 2) The technology used in learning is dominated by virtual reality/lab (35%); 3) Most of the links with cognitive psychology are devoted to conception (33%), and; 4) Physics concepts that are widely used in research are dominated by concepts related to electricity and magnetism (27%). The results of this review indicate that research on cybergogy directly in physics learning is still minimal. However, if it is generalized to research on technology in physics learning over the last five years, it can be seen that the trend is quite good. Thus, the results of this review recommend further research in developing technologies that are popular in physics learning cybergogy, such as the development of virtual reality/lab or Augmented Reality.